Literary translation in Galicia during the dictatorship (1936-1975), a challenge to public authority. The first translation into Galician of "Platero" - Fernández Rodríguez, Áurea (Madrygal. Revista de Estudios Gallegos, 2013)
The analysis of Platero y yo first translation into Galician during the dictatorship serves as a basis to argue that the sociological conditions, while essential, fail to explain all the difficult work of translation. We therefore opted for a flexible model capable of integrating all human and nonhuman mediators as understood by the Actor Network Theory (ANT). We are also able to go back to a document whose message is still valid today, so that we can establish a parallel between his message in the hostile context of our present history, with the current threat situation for a minority culture such as the Galician there are two separate phenomenas in which we are living in the XXI century: the globalization and the birth of a new reality, the dictatorship of the big markets.
Keywords: dictatorship; the process of translation; minority culture; actor network theory